If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3x + -1x + 3 Reorder the terms: 7 = 3 + 3x + -1x Combine like terms: 3x + -1x = 2x 7 = 3 + 2x Solving 7 = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + -2x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -2x = 3 + 0 7 + -2x = 3 Add '-7' to each side of the equation. 7 + -7 + -2x = 3 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 3 + -7 -2x = 3 + -7 Combine like terms: 3 + -7 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| -14=-3x+7x+10 | | 20-4x=-6x+12 | | (n-2)180=60 | | -4+4x+6x=-54 | | 7x+6+6x=110 | | t/-12=-4/15 | | -2*-4=5+8 | | -6+6x-4x=16 | | x^2-4ax-2=0 | | -5x+7+2x=-8 | | 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 |